PENGARUH TRUST, PRIVACY, DAN QUALITY OF SERVICE TERHADAP KEBERHASILAN E-CRM MELALUI CUSTOMER SATISFACTION PADA PENGGUNAAN E-WALLET - Perdana, Wahyu Goesty Perdana; Welsa, Henny; Ningrum, Nonik Kusuma (Jurnal Ilmiah Ekonomi Dan Bisnis, 2024)
E-wallet is a popular payment system in society due to technological advancements causing disruption. This research was conducted to study the success of E-CRM (Electronic Customer Relationship Management) among e-wallet users in terms of Trust, Privacy, and Quality of Service, with Customer Satisfaction as a mediating variable. This study employed a quantitative method with a sample size of 190 respondents. Data were tested through descriptive analysis and multiple linear regression. Findings revealed that Trust does not have a relationship with E-CRM. Service quality and privacy influence E-CRM, where all three variables trust, privacy, and quality of service have a significantly positive impact on customer satisfaction. This research provides information regarding the influence of trust, privacy, and service quality on the success of E-CRM systems through customer satisfaction in using e-wallets. It is highly valuable and can be considered for the implementation of E-CRM